Kedudukan Organ RUPS Dalam Badan Hukum Perseroan Perorangan - Abigail Prasetyo (Jurist-Diction, 2023)
AbstractRegulations regarding the individual companies as written in the Job Creation Act, has a new perspective of concept. Which is, the possibility to have a single shareholder in a company. However, this perception could drive a new problem, especially concerning the GMS organ, which essentially given the capacity as the policy maker within the company. The problems that would arise from shares that were only owned by a single person, also what is the role of GMS organ in this individual company will also be discussed further in this article. This article uses the normative legal research method, with a conceptual approach from theory of organs. In conclusion, it explains that there are only two organs in an individual company. While the GMS organ only relies on one which also holds the role of director. Nevertheless, it can open opportunities for the organs to make decision subjectively for the company.Keywords: GMS, Private Company, Creation Labor Act and Organ Theory. AbstrakPengaturan mengenai Perseroan Perorangan yang diatur dalam UU Cipta Kerja, memberikan konsepsi bahwa dimungkinkannya pemegang saham tunggal dalam sebuah perseroan. Akan tetapi, keadaan demikian dapat menimbulkan permasalahan baru, khususnya menyangkut organ RUPS yang pada hakikatnya menjadi pembuat kebijakan di dalam Perseroan. Apakah permasalahan yang dapat timbul dari kepemilikan saham yang hanya dipegang oleh satu orang saja, serta bagaimana peranan organ RUPS dalam hal Perseroan Perorangan menjadi hal yang hendak dibahas lebih lanjut lama artikel ini. Untuk menjawab rumusan tersebut, Penulis menggunakan metode penelitian hukum normatif dengan pendekatan konseptual dari teori organ dalam badan hukum. Pada akhirnya, Penulis menyimpukan bahwa dalam Perseroran Perorangan organ RUPS yang hanya bertumpu pada satu pemegang saham, secara otomatis merangkap kedudukannya sebagai direksi juga. Oleh karenanya, resiko terkait peluang penyalahgunaan kekuasaan dalam menentukan kebijakan menjadi sangat subjektif.Kata Kunci: RUPS, Perseroan Perorangan, UU Cipta Kerja dan Teori Organ.